2021
DOI: 10.1113/ep089975
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐maximal aerobic exercise training reduces haematocrit and ameliorates symptoms in Andean highlanders with chronic mountain sickness

Abstract: Excessive erythrocytosis is the hallmark sign of chronic mountain sickness (CMS), a debilitating syndrome associated with neurological symptoms and increased cardiovascular risk. We have shown that unlike sedentary residents at the same altitude, trained individuals maintain haematocrit within sea-level range, and thus we hypothesise that aerobic exercise training (ET) might reduce excessive haematocrit and ameliorate CMS signs and symptoms. Eight highlander men (38 ± 12 years) with CMS (haematocrit: 70.6 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Our study showed that LI and MI exercises improve O 2 transport without erythrocytosis. Participants in the LI and MI groups experienced an increase in trueV˙ $\dot{\mathrm{V}}$O 2peak after the intervention, consistent with a previous study finding that exercise training in highlanders can successfully improve aerobic capacity and exercise workload (Macarlupu et al., 2021). Additionally, we found that LI exercise increased CO, as has been reported previously (Nystoriak & Bhatnagar, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that LI and MI exercises improve O 2 transport without erythrocytosis. Participants in the LI and MI groups experienced an increase in trueV˙ $\dot{\mathrm{V}}$O 2peak after the intervention, consistent with a previous study finding that exercise training in highlanders can successfully improve aerobic capacity and exercise workload (Macarlupu et al., 2021). Additionally, we found that LI exercise increased CO, as has been reported previously (Nystoriak & Bhatnagar, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…A possible additional limitation to our study is the contribution of age to the variation in peak V̇ o 2 . Analysis of pooled data from our study and two different studies in male highlanders from Cerro de Pasco in the age range 24–64 yr ( 30 , 56 ) shows a weak but significant correlation between peak V̇ o 2 and age ( r = 0.33, P < 0.05, n = 43). Although we did not observe this association in our sample, possibly due the reduced number of participants, age was not an intrastudy determinant of peak V̇ o 2 neither in the non-EE nor the EE group both pre- or post-IVHD (either separate or combined), and thus can be considered as a uniform variable.…”
Section: Discussionmentioning
confidence: 46%